Transformasi Warak Ngendhog Menjadi Tari Warak Dhugdher Di Kota Semarang (Universitas Negeri Semarang, 2020)
Warak ngendhog was originally a toy that was sold and then used as a mascot for the dhugdheran procession. The change later happened that Warak Ngendhog was used as a source of inspiration for the artist to create the Warak Dhugdher dance. Since its presence, the dance brings influence in the city of Semarang. This influence led to the emergence of new forms of Warak dance. This fact shows that the Ngendhog Warak underwent a change to dance Warak Dhugdher. This research aims to identify the form of transformation that occurred and explain the progress of dance Warak Dhugdher. This research is a qualitative study using the etnokoreological approach, which is a dance analysis system that is not merely discussing textual, but also contextual. Analysis of transformation using adaptation theory. The results showed that transformation occurred due to the adaptation process manifested through the creation of dance. Forms of transformation that occur include textual and contextual transformations. Textual transformation is manifested from the addition of the dance choreography aspect as an art show. Warak as property on the dance changes on the structure of the head shape, stomach pattern, and absence of Endhog. The contextual transformation that occurs indicates a change in form, meaning, and function that causes development. The Warak transformation of Ngendhog does not stop at the dance form of Warak Dhugdher, but it can develop into another Warak dance form.